Study guides

☆☆

Q: What is the square root of x if it equals to 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

(x^2+x-1/2)= x(x+1)-1/2 [x + (1 - square root of 3)/2][x + (1 + square root of 3)/2] = 0 Check it: x^2 + x/2 + (square root of 3)x)/2 + x/2 + 1/4 + (square root of 3)/4 - (square root of 3)x/2 - (square root of 3)/4 - 3/4 = 0 x^2 + x/2 + x/2 + [(square root of 3)x]/2 - [(square root of 3)x]/2 + (square root of 3)/4 - (square root of 3)/4 + 1/4 - 3/4 = 0 x^2 + x - 2/4 = 0 x^2 + x - 1/2 = 0 How to find this roots: Using the completing the square method: x^2 + x - 1/2 = 0 x^2 + x = 1/2 x^2 + x + 1/4 = 1/2 + 1/4 (x + 1/2)^2 = 3/4 x + 1/2 = (plus & minus)(square root of 3/4) x = -1/2 + (square root of 3)/2 x = - 1/2 - (square root of 3)/2

31 x 31 = 961 31 is the square root of 961.

what is the domain of g(x) equals square root of x plus 1? √(x+1) ≥ 0 x+1≥0 x≥-1 Domain: [-1,∞)

root 27 = root 9 x root 3 = 3 root 3. Dividing this by root 3 gives 3!

√3 x √27 = 9

Related questions

x = 9

Yes, because when x equals 1, the square root of x is rational and the square root of -x is irrational, and when x equals -1, the square root of x is irrational and the square root of -x is rational.

x = 7

6 Square root of 4 equals 2 3 x 2 = 6

x = square root of 3.

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

If x equals the square root of ...., then you already have solved for x

Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3

X = 81 sqrt(X) + 3 = 12 ( subtract 3 from each side ) sqrt(X) = 9 (square both sides ) X = 81 ( the square root of 81 is 9 )

The square root of a value v is a number x such that, x multiplied by x equals v. Note that -x is also a square root.

If: x2 = 3 Then: x = square root of 3

0.019245009 or square root of 3 divided by 30

People also asked